Electrochemical Determination of diethylstilbestrol at glassy carbon electrode modified with gold nanoparticles and a film of multi-wall carbon nanotubes and cobalt phthalocyanine - Janmille da Silva AragÃo (2016)
This paper describes the development of an electrochemical sensor glassy carbon modified with gold nanoparticles and a film of multiâwalled carbon nanotube and cobalt phthalocyanine (CoPc-fMWCNTs/AuNp/GCE) for the determination of diethylstilbestrol hormone (DES) in water samples and meat, using a square wave technique voltammetry. (SWV). The electrolyte used was Britton-Robinson buffer (BR) 0.04 mol L-1 pH 10.0. Initially it was studied the electrode configuration to be used for the development work, after the optimization of solution pH, study scan speed to evaluate the charge transfer kinetics in the redox process of the DES, the optimized parameters for SWV, the analytical curve, and finally, applying the methodology developed. The optimized parameters for SWV were f = 5 sâ1, a = 50 mV and ΔEs=1 mV. The CoPc-fMWCNTs/AuNp/GCE was ready to be used for the application since all conditions were optimized. Analytical curves were obtained in the concentration ranged from 7.9365 Ã 10−7 â 5.6604 Ã 10−6 mol Lâ1 (R = 0.9996) and there were obtained limits of detection (LOD) and quantification (LOQ) of 1.9910 x 10â7 mol Lâ1and 6.6367 x 10â7 mol Lâ1, respectively, being comparable to those reported in the literature. The repeatability and reproducibility of the proposed procedure were evaluated. The relative standard deviation (RSD) were 4.33% and 3.49%, respectively, indicating the precision of the assay. The recovery percentage was 98.56% for the water sample and 94.05% for beef sample (RSD of 0.40 and 1.55% respectively). The modified electrode has developed sensitivity, reproducibility and repeatability appropriate and consistent LOD and LOQ values with those reported in the literature. Moreover, the results obtained by the use of CoPc-fMWCNTs/AuNp/GCE proved very efficient as the detection and DES recovery, being thus a promising device in the detection and quantification of DES in water samples and food.